Sewage workers: risk of acquiring enteric virus infections including hepatitis A - Divizia, Maurizio; Cencioni, Barbara; Palombi, Leonardo; Panà, Augusto (The New microbiologica, 2008)
To determine if sewage workers have an increased risk of acquiring viral infections, 66 workers at a small wastewater plant in north-eastern Italy and 72 control subjects recruited from blood donors were enrolled in a seroprevalence study to determine whether sewage workers are at increased risk of acquiring viral infections. In order to evaluate various risk factors, a questionnaire was filled out by each worker whereas seropositivity to Hepatitis A virus, Coxsackievirus B2 - B3 - B4 - B5, and Echovirus types 1 and 9 was determined in the laboratory. Anti-HAV antibodies were present in 37.8% of sewage workers and 36.1% of subjects in the control group. The difference was not statistically significant in the two groups, whereas a significant association was observed regarding age (P < 0.3). No association was observed with the occupational age, or with number and duration of contacts per day. The lack of evident occupational risk for hepatitis A among sewage workers may be explained by the adult age of the workers (mean age 41.3 years, range 22-58 years), and thus the antibody titre against different enteroviruses was determined. No statistically significant differences were evident with the raw values, but considering the 90 degrees percentile as a dichotomic value for the antibody levels a strong and significant association was present with Coxsackievirus B3 (O.R. 22.85, C.I. 95% 2.93-178.08) and Coxsackievirus B2 (O.R. 14.25, C.I. 95% 1.78-113.87). Analysis of the data confirms a limited risk of acquiring infection and/or disease but also the evident possibility of silent exposure to the viruses. The shift in HAV epidemiology and increased morbidity and mortality in adult age suggest that active immunization against hepatitis A should be considered.